Modeling, design and manufacturing of an acoustic levitation linear transportation system. - Thomas, Gilles Pierre Loïc (2015)
Acoustic levitation is a method which uses sound radiation to suspend matter in a medium. The main use of this phenomenon is for the contactless processing of matter, allowing to manipulate small objects without any solid contact. Contactless processing of matter presents many advantages in, for example, the fabrication of MEMS (microelectromechanical systems) where handling the components is challenging because of their fragile and surface-sensitive characteristics or in the chemical/biological industry when handling high-purity or hazardous materials. Thus, a new device for noncontact linear transportation of small solid objects is presented here. In this device, ultrasonic flexural vibrations are generated along the ring shaped vibrator using two Langevin transducers and by using a reflector parallel to the vibrator, small particles are trapped at the nodal points of the resulting acoustic standing wave. The particles are then moved by generating a traveling wave along the vibrator, which can be done by modulating the vibration amplitude of the transducers. The working principle of the traveling wave along the vibrator has been modeled by the superposition of two orthogonal standing waves, and the position of the particles can be predicted by using finite element analysis of the vibrator and the resulting acoustic field. A prototype consisting of a 3 mm thick, 220 mm long, 50 mm wide and 52 mm radius aluminum ring-type vibrator and a reflector of the same length and width was built and small polystyrene spheres have been successfully transported along the straight parts of the vibrator.